Lipoteichoic Acid of Probiotic Lactobacillus plantarum Attenuates Poly I:C-Induced IL-8 Production in Porcine Intestinal Epithelial Cells - Kim, Kyoung Whun; Kang, Seok-Seong; Woo, Sun-Je; Park, Ok-Jin; Ahn, Ki Bum; Song, Ki-Duk; Lee, Hak-Kyo; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Microbiology, 2017)
Probiotics in livestock feed supplements are considered a replacement for antibiotics that enhance gastrointestinal immunity. Although bacterial cell wall components have been proposed to be associated with probiotic function, little evidence demonstrates that they are responsible for probiotic functions in livestock. The present study demonstrated that lipoteichoic acid of Lactobacillus plantarum (Lp.LTA) confers anti-inflammatory responses in porcine intestinal epithelial cell line, IPEC-J2. A synthetic analog of viral double-stranded RNA, poly I:C, significantly induced IL-8 production at the mRNA and protein levels in IPEC-J2 cells. Lp.LTA, but not lipoprotein or peptidoglycan from L. plantarum, exclusively suppressed poly I:C-induced IL-8 production. Compared with lipoteichoic acids from other probiotic Lactobacillus strains including L. delbrueckii, L. sakei and L. rhamnosus GG, Lp.LTA had higher potential to suppress poly I:C-induced IL-8 production. Dealanylated or deacylated Lp.LTA did not suppress poly I:C-induced IL-8 production, suggesting that D-alanine and lipid moieties in the Lp.LTA structure were responsible for the inhibition. Furthermore, Lp.LTA attenuated the phosphorylation of ERK and p38 kinase as well as the activation of NF-kB, resulting in decreased IL-8 production. Taken together, these results suggest that Lp.LTA acts as an effector molecule to inhibit viral pathogen-induced inflammatory responses in porcine intestinal epithelial cells.